Analysis of chief complaint, toothbrushing, plaque score, dental care program and decay in children - Supaat, Salwana; Witjaksono, Widowati; Sukmasari, Susi (2013)
The objective of this study was to investigate association between chief complaint, tooth brushing frequency, plaque score, dental care program in school (DCPIS) and decay. There was a cross sectional study on randomized of 113 children attended to Student Dental Clinic at International Islamic University Malaysia. The study were done following the ethical issue of university. Patient’s date of birth, gender, chief complaint, brushing habits, plaque score, and DCPIS were recorded. Decay were recorded using a blunt probe, dental mirror and clear illumination. A descriptive statistical study was carried out. Differences between group were tested using chi-square (p<0.05). The study showed 45.1% boys and 54.9% girls. Range of age were 4 till 15 years old and mean was 9.266 ( 0.4998). Chief complaint was 69.9% for dental check up, and 30.1% complaint of pain, orthodontic treatment or trauma. Children that has been received DCPIS were 69.9%, never or didn’t know were 30.1%. Children had irregular or didn’t know the tooth brushing frequency, one time, twice, and more than twice a day were 13.3%, 17.7%, 46.9% and 22.1% respectively. Subjects had high plaque score, moderate and low were 91.2%, 3.5% 5.3% respectively. Mean of tooth decayed were 4.778 (sd. 3.379). There were no significant association between plaque score, chief complaint and decay. There were a significant association between tooth brushing frequency, plaque score and dental care program in school. Key Word: Chief complaint, Tooth brushing frequency, Plaque score, Dental care program in school, Decay.